Reporting violence to police: a survey of victims attending domestic violence services - Emma Birdsey
Aim: The aim of the study was to investigate what proportion of domestic violence (DV) victims who seek help from DV services choose not to report the violence to police and to investigate factors and reasons associated with non-reporting.Method: Data was collected by interviewing 300 victims attending DV services. The interview was conducted by telephone and included questions on (a) victim characteristics, (b) characteristics of victims’ most recent incident, and (c) victims’ reasons for not reporting to police. Descriptive and bivariate analyses were undertaken to determine characteristics associated with the decision to report a domestic violence incident to police.Results: Approximately half (51.8%) of victims reported their most recent incident to the police. Victims were more likely to report if they had an AVO against the offender, if their property had been damaged, if they were physically injured, if the abuse was physical or sexual, if they felt their children were at risk or if they had reported previous DV incidents. Victims were less likely to report if they were pregnant or experienced more than 5 previous incidents of abuse. The top three reasons for not reporting to police were fear of revenge/further violence (13.9%), embarrassment/shame (11.8%), or the incident was too trivial/unimportant (11.8%). The primary barrier to reporting, according to those interviewed, is that police either do not understand or are not proactive in handling DV (17.1%).Conclusion: Half of victims reported DV to the police, leaving the remainder without official legal intervention and professional support